The Syntax Features of the African American English In Georgia Doyle Johnson’s Frederick Douglas And Loraine Hansberry’s A Raisin in the Sun - Sadiq, Nizamuddin (Journal of English and Education (JEE), 2008)
Syntax reflects features of a language. One of the American African English features in syntax can be seen in Georgia Doyle Johnson’s Frederick Douglas and Loraine Hansberry’s A Raisin in the Sun. As it is considered non-standard dialect, the American African English syntax is assumed to have its own characteristic different from the standard American English. This paper is descriptive linguistics rather than a stylistic study as it does not focus on literary style. The data taken was classified into linguistic elements and was" tested to the theories of informal English in general; African American English in particular and Standard American English rules of pronunciation. The research findings were summarized and discussed to conclude the research. The result of the research demonstrates that African American English, a variant of informal English, is different from the rules of Standard American English. In terms of syntax, the African American English style if it is seen from viewpoint of grammar function contradicts with features-6f Standard English: clarity^ brevity and fluency. The rules of clarity are broken by the presence of ellipses, clippings, copulas and tenses; brevity by the presence of unnecessary repetition and additions; and fluency by the presence of combinations of assimilation and clipping. African American English speakers employ polite expressions. The research revealed that polite expressions when greeting people, using please when asking for permission and using titles to show respect is done, particularly with elders. Furthermore, when the speaker is angry, she/he uses a complete name for emphasis.